2022
DOI: 10.1111/nph.18103
|View full text |Cite
|
Sign up to set email alerts
|

Climate drives patterns of seed traits in Quercus species across China

Abstract: Traits enabling seeds to survive post-dispersal desiccation and subsequently germinate are important aspects of plant regeneration for species with desiccation-sensitive seeds. However, how desiccation and germination-related traits co-vary and relate to patterns of climate variation are unknown.We investigated physiological traits related to desiccation and germination of desiccationsensitive seeds from 19 Quercus species, which typically dominate subalpine, subtropical and temperate forests in China.The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Previous studies investigating Q. variabilis have mainly focused on its morphological characteristics (Du et al, 2021;Sun et al, 2021), its responses and adaptations to climate change (Gao et al, 2020;Xia et al, 2022), or its adaptive evolution and introgression, as assessed using whole genome resequencing (Fu et al, 2022). However, to date, no nuclear genomic resources are available for Q. variabilis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating Q. variabilis have mainly focused on its morphological characteristics (Du et al, 2021;Sun et al, 2021), its responses and adaptations to climate change (Gao et al, 2020;Xia et al, 2022), or its adaptive evolution and introgression, as assessed using whole genome resequencing (Fu et al, 2022). However, to date, no nuclear genomic resources are available for Q. variabilis.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that acorns maturing in different environments may show different responses to drying, regardless of the reason. This view is shared by Xia et al [66], who showed that acorns of Quercus from cold regions are more desiccation-sensitive than those from warmer areas. As a common feature across Fagaceae, the maternal environment in which the acorns mature influences their survival during drying.…”
Section: Discussionmentioning
confidence: 82%
“…In terms of seed storage, all oaks studied to date have recalcitrant seeds (Xia et al, 2012(Xia et al, , 2022Royal Botanic Gardens Kew, 2022); consequently, traditional long-term ex situ conservation in seed banks is not possible and thus require cryobiotechnological approaches (Walters et al, 2013;Ballesteros and Pritchard, 2020). Seed embryonic axes (with shoot and root meristems) are the preferred explants for oak cryopreservation as, analogously to conventional seed banking, high genetic diversity can be captured and axes can be grown into full plants with relatively simple micropropagation procedures (Ballesteros and Pritchard, 2020).…”
Section: Seed and Pollenmentioning
confidence: 99%
“…However, this environmentally-modulated response to cryopreservation of the oak seeds may not be shared among all species. For example, another study indicated that seed of subalpine oak species from China were most desiccation sensitive and died faster when dried than subtropical and temperate oak from the same country (Xia et al, 2022), suggesting the opposite trend found for North American and Mediterranean species (Xia et al, 2012;Amimi et al, 2020).…”
Section: Seed and Pollenmentioning
confidence: 99%